1995
DOI: 10.1002/joc.3370150304
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic surface energy balances for different climate types

Abstract: An attempt is made to answer the question of whether the different climate types of the Koppen-Geiger classification are also characterized by distinct annual courses of the surface energy balance terms. For this purpose the KoppenGeiger climate map was linked with Budyko's atlas of the heat balance of the Earth. For every climate area shown on the Koppen-Geiger map (and classified by a certain combination of up to three letters) the annual course of the energy balance terms was extracted from Budyko's atlas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Koeppen's system is useful for climate research, as shown by Fraedrich et al (2001) for continental climate shifts, seasonal variation of climate boundaries in the USA (Suckling and Mitchell, 2000), and comparative pedological research (Bockheim, 2005). Also, Koeppen's classified climates describe different surface-energy balances (Kraus and Alkhalaf, 1995) and are used in model testing and calibration, as shown by Nonomura et al (2003) for vegetation cover in Africa, and by Kalvova et al (2003) in general circulation models. Most criticisms of Koeppen's system are related to the rigid boundary criteria (Stern et al, 2000) that, in some cases, include diverse natural landscape features in the same climate class, as a result there is a strong internal variability of important climate elements (Triantafyllou and Tsonis, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Koeppen's system is useful for climate research, as shown by Fraedrich et al (2001) for continental climate shifts, seasonal variation of climate boundaries in the USA (Suckling and Mitchell, 2000), and comparative pedological research (Bockheim, 2005). Also, Koeppen's classified climates describe different surface-energy balances (Kraus and Alkhalaf, 1995) and are used in model testing and calibration, as shown by Nonomura et al (2003) for vegetation cover in Africa, and by Kalvova et al (2003) in general circulation models. Most criticisms of Koeppen's system are related to the rigid boundary criteria (Stern et al, 2000) that, in some cases, include diverse natural landscape features in the same climate class, as a result there is a strong internal variability of important climate elements (Triantafyllou and Tsonis, 1994).…”
Section: Introductionmentioning
confidence: 99%